MENYINGKAP ILMU PERUBATAN MELAYU TRADISIONAL MENERUSI BEBERAPA MANUSKRIP TERPILIH - Mohd Noor, Arba'iyah (SEJARAH: Journal of the Department of History, 2017)
Large numbers of manuscripts on Malay traditional medicine in the Malay Archipelago are located in Malaysia as well as in few European libraries. This situation demonstrates that the Malay traditional medicine has been both practised and documented to be used as guidelines for the next generation. These medical manuscripts reflect the Malay’s knowledge and expertise in identifying types of diseases, remedies, and its subsequent treatments on diseases that affect the natives. This article discusses Malay traditional medicine based on selected Malay manuscripts, including that of medicinal and historical accounts that included medical services by Malay medical practitioners. Aspects that will be focused upon are historical account of Malay medicines pre- and post-Islam, medical services by Malay medical practitioners, types of diseases, medicines and methods of treatment in treating diseases.